Practical tips for teaching medicine in the metaverse [version 3; peer review: 2 approved, 3 approved with reservations] - Manuel Maynar; Miguel Angel Rodriguez-Florido (MedEdPublish)
The metaverse is based on immersive technologies such as virtual and augmented reality, body tracking, tactile sensation, etc. A growing number of studies are demonstrating the potential of the metaverse as an attractive resource for learning medicine. However, in practice, medical teachers and students often encounter significant challenges when utilizing the underlying technologies, potentially leading to frustrating learning experiences. A significant part of the teaching time is often devoted to troubleshooting technical issues with the metaverse, and the medical content itself taking a backseat until students become proficient in navigating the metaverse environment. Therefore, it is essential to fit the metaverse's underlying technologies specifically for medical education, minimizing technical hurdles for both teachers and students. In this paper, we deal with this challenge and we present a collection of practical tips that serves as a guide for medical educators making decisions in this emerging field, where they may lack prior experience. Drawing on our observation with a cohort of 776 medical students, we conclude how to effectively identify, design, or implement educational applications tailored for efficient medical learning through the metaverse. Our work may support teachers considering metaverse learning platforms for their classrooms and it is a beneficial reference for the medical education community during the initial stages of implementing the metaverse for teaching.